Investigation Audit Analysis of Fraudulent Financial Reporting - Pristy Wulandari; Putri Aditya Lestari; Putri Septiana Br. Sigalingging; Riandi Syahputra; Galih Supraja (Formosa Journal of Social Sciences (FJSS), 2024)
Investigative audit is an important instrument in detecting and exposing financial reporting fraud, including indications of corruption. This audit process includes planning, collecting evidence, analyzing findings, and reporting results comprehensively. This study examines the application of investigative audit techniques, such as reverse proof and in-depth analysis of the modus operandi, causes of deviations, and impacts of violations. The results of the literature study indicate that investigative audits are effective in exposing fraud if carried out with the right method, supported by valid evidence, and the involvement of professional auditors. However, time pressure can affect the auditor's accuracy, thus affecting the quality of findings. Therefore, time management and auditor competency development are key factors in increasing the effectiveness of investigative audits. This study confirms that investigative audits not only play a role in detecting fraud but also support asset protection and improvement of the organization's internal systems